Development Policy of the International Trade Industry under the Background of Cloud Computing and Internet of Things. (2nd June 2022) - Wu, Liang; Zhou, Jianhua; Tang, Honglei; Xiao, Hanjie
Abstract : With the continuous development of Internet technology, new opportunities and challenges have emerged in international trade. If it does not seize new opportunities and take measures to meet challenges, it will cause the development of international trade to enter a state of stagnation, especially when the current domestic demand has not shown a strong recovery. The emergence of cloud computing and the Internet of Things (CCIoT) has provided new technologies and means for the development of international trade. In order to accurately analyze the development policy of the international trade industry and provide strong technical support for the development of the international trade industry under the Internet of Things environment, this paper studies the development policy of the international trade industry in the context of CCIoT. This paper borrows the method of cloud computing and collects relevant data provided by development policies through the perception Internet layer. It is transmitted through the network layer, processed through the high-performance computing cloud, and finally transformed into useful information for the international trade industry. The test results show that the use of cloud computing technology can analyze the existing development policies, promote the development of the international trade industry, and improve the trade efficiency by 3.84%. This reduces the impact of various factors on international trade, while providing strong and good services to users in international trade.